UPAYA PENGEMBANGAN DAN PEMBERDAYAAN PETERNAK SAPI BALI POTONG SISTEM PERKANDANGAN DI KECAMATAN DOLO KABUPATEN SIGI - Pariyati Pariyati; Rukhayati Rukhayati (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2022)
Beef cattle farming business can be said to be successful if the business contributes income and can meet the daily needs of farmers. Currently, beef cattle farming is mostly carried out by the community, so that it opens and absorbs workers. Livestock business can be the foundation of family income (source of income). handling livestock as a series of activities, through community service activities that are carried out independently, is expected to open up public insight through beef cattle farming. Food self-sufficiency in a broad sense is not only in rice, but includes the total food needs of the people. The success of widespread food self-sufficiency is expected to encourage the creation of sustainable food sources